Strange attractors : lives changed by chance - Meidav, Edie, 1967-; Dropkin, Emmalie (University of Massachusetts, 2019)
"Has a stunning surprise or lucky encounter ever propelled you in an unanticipated direction? Are you doing what you always thought you would be doing with your life or has some unseen magnetism changed your course? And has that redirection come to seem inevitable? Edie Meidav and Emmalie Dropkin asked leading contemporary writers to consider these questions, which they characterize through the metaphor of "the strange attractor," a scientific theory describing "an inevitable occurrence which arises out of chaos." Meidav's introduction and the thirty-five pieces collected here offer imaginative, arresting, and memorable replies to this query, including guidance from a yellow fish, a typewriter repairman, a cat, a bear, a bicycle, and a Buddhist professor of writing. Absorbing and provoking, this is nonfiction to be read in batches and bursts and returned to again and again"--